2014
DOI: 10.1111/aji.12288
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast Induces Monocyte Differentiation Into CD14+/CD16+ Macrophages

Abstract: Problem During early pregnancy, macrophages and trophoblast come into close contact during placenta development, and regulated cross talk between these cellular compartments is crucial for maintaining a healthy pregnancy. As trophoblast cells constitutively secrete many chemokines and cytokines, we hypothesize that trophoblast secreted factors can differentiate monocytes into a decidual phenotype. In this study, we describe a unique macrophage phenotype following monocytes’ exposure to trophoblast soluble fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 50 publications
3
59
0
1
Order By: Relevance
“…22,41 It is interesting to note that exposure of macrophages to severe hypoxia for 48 hours abolished Hif1a mRNA expression (Figure 3). 6 Another limitation is that we did not include other cell types that might cross-talk with macrophages, such as trophoblast cells 44,45 and endothelial cells, as they may also regulate angiogenic function of macrophages. In our study, we treated M2 cells with different doses of progesterone and estradiol within the range found at the feto-maternal interface.…”
Section: Discussionmentioning
confidence: 99%
“…22,41 It is interesting to note that exposure of macrophages to severe hypoxia for 48 hours abolished Hif1a mRNA expression (Figure 3). 6 Another limitation is that we did not include other cell types that might cross-talk with macrophages, such as trophoblast cells 44,45 and endothelial cells, as they may also regulate angiogenic function of macrophages. In our study, we treated M2 cells with different doses of progesterone and estradiol within the range found at the feto-maternal interface.…”
Section: Discussionmentioning
confidence: 99%
“…As these cells encounter various maternal immune cells, particularly CD14 1 myelomonocytic cells, interactive cross-talk between the cellular compartments is critical for maternal-fetal tolerance [17][18][19]31 . Previous studies have shown that trophoblast cells express a wide range of chemokines and cytokines, which induce CD14 1 myelomonocytic cell differentiation into special subtypes with higher levels of IL10 and increased capacity for phagocytosis 31,32 . We have performed several functional analyses, revealing that HTR8/SVneo cell-induced CD14 1 HLA-DR 2/low cells effectively inhibited the expansion of CD3/ CD28-activated autologous CD4 1 T cells (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Assays were performed according to the manufacturer's instructions as previously described 12, 13, 14. Cartridges containing IL‐6, IP‐10, TNF‐α, and IL‐1β were run alongside the Luminex plates, and data were converted from relative units/RFU to concentration (pg/ml) to directly compare formats.…”
Section: Methodsmentioning
confidence: 99%